Distinctive Features of Microcrystallization of Mixed Saliva in Children with Different Levels of Activity of Carious Process - Irina, M. Voloshina (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Microcrystallization of oral fluid is one of the main indicators of mixed saliva. Introduction: This method allows to identify the effectiveness of preventive and therapeutic measures carried out in the oral cavity. Materials and Methods: The clinical material of 187 patients was analyzed. Oral fluid was analyzed on the basis of the following parameters: pH, general concentration of Ca and P, velocity of secretion, mass of sediment; microcrystallization was analyzed too. The study was carried out in the following terms: before the treatment of caries, after the sanitation of the oral cavity, every month for six months. Results and Discussion: Clinical and laboratory studies have shown that children with different intensity of the carious process revealed a number of features of mixed saliva.